Carbon tax and trading mechanisms for emission reduction in the Indonesian power sector - Wahri Sunanda; M. Isnaeni Bambang Setyonegoro; Sasongko Pramono Hadi; Sarjiya (Cleaner Engineering and Technology)
The Indonesian power sector is predominantly dependent on coal and vital to the net-zero emissions (NZE) goals of the country. Therefore, this study examined the efficiency of carbon tax and trading mechanisms in mitigating CO2 emissions. This assessment employed the Integrated MARKAL-EFOM System (TIMES) model to explore three carbon tax scenarios [USD 2/tCO2 (CT-2), USD 63/tCO2 (CT-63), and USD 127/tCO2 (CT-127)] and two emissions trading schemes (conditional and unconditional caps) following the Indonesian Enhanced Nationally Determined Contribution (ENDC). Consequently, CT-63 [446.93 million metric tons of CO2 (MtCO2 )] and CT-127 (264.85 MtCO2) demonstrated the most significant emission reductions by 2050. Although these scenarios facilitated a transformative transition to renewable energy (RE), a substantial financial burden was observed with these reductions. One notable example was CT-127, which was anticipated to prevail with 1,404.88 TWh of RE but necessitated a cumulative capital investment of USD 962 billion by 2050. The emissions trading schemes (particularly cap-conditional) also provided a cost-effective option, attaining moderate reductions with a renewable share of 90.75% by 2050. Nevertheless, these schemes might not fulfill more ambitious climate objectives. Despite the findings of this study revealing that high carbon taxes were highly influential for deep decarbonization, a synergistic strategy combining rigorous carbon taxes with emission restrictions could align emission reduction objectives with investment viability. Overall, decisive and definitive carbon pricing regulations could facilitate the Indonesian energy transformation to enable the power sector to achieve ENDC and NZE objectives.